Estimation of Serum Sialic Acid in the Patients of Type-2 Diabetes Mellitus - Sofia Chandio, Nazish Shafi, Maria Asif, Fahad Aman Khan, Sindhu Laghari, Ali Raza Memon, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Diabetes Mellitus is one of the leading cause of morbidity & mortality all over the world. The poor glycemic control in the patients of type-II diabetes mellitus can lead the development of complications which cause the morbidity in the life of diabetic population. The aim of this study was to estimate the serum sialic acid in the patients of type- II diabetes for early prediction of diabetic complications. Methodology: This case comparative study was conducted at the Diabetes Clinic of LUMHS Jamshoro with the collaboration of the Department of Biochemistry at LUMHS. A total of 84 diagnosed cases of type-II Diabetes Mellitus were included in this study. In group A, 40 diabetes mellitus cases were diagnosed with a history of diabetes less than five years, while in group B 44 had histories of diabetes over ten years. Spectrophotometers were used to measure serum sialic acid levels using Ehrlich's reagent. SPSS version 22 was used for data analysis with independent student t tests applied. Results: The mean serum sialic acid level of group A was 56.42 ± 5.67 mg/dl, while serum sialic acid level of group B was 69.88 ± 7.34 mg/dl. There was significant (p<0.05) increased level of serum sialic acid in the type-II diabetic patients of group B, which indicate there is more chance to development of micro vascular complications in type-II diabetic patients with prolong duration for their diseases period. Conclusion: Estimation of serum sialic acid in the patients of type-II diabetes mellitus is one of the early predictive marker for the complications of diabetes mellitus.